Initial Assessment on Students Perception Towards Campus Sustainability - Datu Razali Datu Eranza; Lee, Andy Chen Hiung; Tini Maizura Mokhtar (Universiti Malaysia Sabah, 2017)
This paper is an opinion piece on the initial assessment of the comprehension of Universiti Malaysia Sabah (UMS) students‟ knowledge about UMS EcoCampus programs in the context of campus sustainability, and their suggestions for green initiatives. A total number of more than 350 students were sampled. The students were divided into a working group and worked on abstracts related to campus sustainability. A total number of 35 groups were formed as units of analysis for this study. The assessment process was conducted in four meetings over a one-month period after lecture. For data collection, the 35 working groups were required to come up with an abstract for each group, and the abstracts were being reviewed by several experts in campus sustainability or personnel familiar with the activities organized by UMS EcoCampus Management Centre. The result suggested that some of the students understood the general concepts of sustainability and some were uncertain about it. The uncertainty is mainly due to the context of „campus‟ sustainability. The sustainability knowledge of students was mostly on recycle and reuse, electronic technology usage in substituting conventional management practices, and “go green” campaigns. Based on the findings, the result indicates that students of UMS would have to be given more exposure on campus sustainability, and it is best to include sustainability element into course syllabus. By then in the near future, the graduates will be “greener” and susceptive to the concept of sustainability.